Nurse manager intentional rounding and outcomes: Findings of a systematic review. (24th May 2022) - Bayram, Aysun; Özsaban, Aysel; Longhini, Jessica; Palese, Alvisa
Abstract: Aim: To summarize the evidence available on Nurse Manager Intentional Rounding (NMIR) describing the main characteristics and methodological quality of studies available, the features of rounding and the outcomes as measured to date. Design: A systematic review. Data Sources: Electronic databases, including MEDLINE‐EBSCHOST, PubMed, CINAHL, Scopus, Cochrane, Clinicalkey, ScienceDirect, OVID, Sage Journals and Web of Science, were searched up to June 2021. Review Methods: The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement guideline was used to summarize methods and report findings. The Joanna Briggs Institute Critical Appraisal tools were used to evaluate the methodology quality of the studies included. Results: Seven studies were included with pre‐post‐test ( n  = 3), longitudinal, two‐group post‐tests, quasi‐experimental, and retrospective study designs ( n  = 1, respectively). In five studies, the nurse managers were trained to conduct the rounding, which was shaped according to three main features: a structured ( n  = 4), a semi‐structured ( n  = 1) and an unstructured rounding ( n  = 2) delivered from high (twice a day 7/7) to low intensity (once a day, 5/7). Two main outcomes have been measured to date, the patient satisfaction and some aspects related to the care quality. Five studies reported that the satisfaction scores of patients who received rounding were significantly higher than that perceived by patients not receiving rounding. About the other aspects of the quality of care, two studies documented significant improvements as a consequence of the NMIR (e.g. information accessibility, discharge instructions, coordination of care after discharge). Conclusion: Studies available report in general a low methodological quality, mainly due to their pragmatic nature as quality improvement projects. Therefore, transforming this field of research by establishing a methodological rigour and a theoretical foundation in both interventions and outcomes and by designing experimental approaches, might expand the evidence available on the effects of nurse managers intentional rounding.